2021
DOI: 10.1007/s00265-020-02946-6
|View full text |Cite
|
Sign up to set email alerts
|

Effective conspecific communication with aberrant calls in the common cuckoo (Cuculus canorus)

Abstract: The obligate brood parasitic common cuckoo (Cuculus canorus) is best known for its two-note “cu-coo” call, which is uttered repeatedly by adult males during the breeding season. This call advertises the male’s claim for his territory. A rare, aberrant version (“cu-kee”) was discovered in a population of cuckoos in central Hungary. In a playback experiment, we simulated conspecific territorial intrusions using either aberrant call sequences or normal calls (as control). Cuckoos responded to both calls similarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…We suppose that these syntax errors are related to the extent of the signal-expression ability of cuckoos, allowing to introduce limited numbers of variations in the sequence and repeat of the elements. Accordingly, the atypical “cu-kee” form 36 can be regarded as an aberrant form of the second note (i.e., not a compositional syntax error), which we found in several individuals.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…We suppose that these syntax errors are related to the extent of the signal-expression ability of cuckoos, allowing to introduce limited numbers of variations in the sequence and repeat of the elements. Accordingly, the atypical “cu-kee” form 36 can be regarded as an aberrant form of the second note (i.e., not a compositional syntax error), which we found in several individuals.…”
Section: Discussionmentioning
confidence: 50%
“…As common cuckoos utter their simple “cu-coo” calls in long series continuously, we hypothesized that the ordering of the two elements and its variants in individual calls would have less relevance than the type of the element. As a previous study 36 already revealed that the first element (“cu”) elicited similar response in receivers as the complete “cu-coo” call, we predicted that the first element (“cu”) would have more information content for male cuckoos’ acoustic communication than the “coo” element. We also predicted that the lack of this element would make the call ineffective for receivers.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Non-passeriform vocalizations are widely assumed to be simple and stereotyped and show little variation; for example, there is a high degree of consistency in the number of syllables (Møller et al, 2016(Møller et al, , 2017 and call characteristics in individual male common cuckoo calls (Jung et al, 2014;Li et al, 2017;Zsebok et al, 2017). However, recent studies have revealed that individual male common cuckoo calls are more variable than previously thought (Deng et al, 2019a), and male common cuckoos can use these versatile vocalizations to encode different messages (Tryjanowski et al, 2018b;Xia et al, 2019;Moskat et al, 2021). Inspired by these observations, our first hypothesis is that female common cuckoos use different calls for interspecific and intraspecific communication.…”
Section: Introductionmentioning
confidence: 99%